Peningkatan Keterampilan Guru PAUD Melalui Kewirausahaan Kreatif Dan Edukatif - Mahardika Agung Madepo; Lina Budiarti; Lidya Verawati (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
Early Childhood Education (ECE) teachers in Indonesia often struggle with a lack of creative teaching materials and low income. This community program aimed to tackle both problems at once through hands-on training in education and entrepreneurship. 30 PAUD teachers from HIMPAUDI Kecamatan Sungai Ambawang, Kubu Raya Regency, joined the program on November 1, 2025. Two main sessions were held: one focused on making Educational Play Tools (EPT) from recycled materials, and another on basic entrepreneurship and digital marketing. Teachers were introduced to the "edupreneur" concept, the idea that educators can create meaningful teaching tools while also building financial independence. During the workshop, participants produced six original EPT products, assessed on creativity, educational value, quality, and marketability, which were then donated to the host school. Feedback from partners across all evaluation areas was rated "Very Good." These results show that combining entrepreneurship training with early childhood education is an effective way to both professionalize teachers and improve their economic wellbeing.